Application of the robot-assisted implantation in deep brain stimulation - Ma, Fang-Zhou; Liu, De-Feng; Yang, An-Chao; Zhang, Kai; Meng, Fan-Gang; Zhang, Jian-Guo; Liu, Huan-Guang (Frontiers in Neurorobotics, 2022)
Introduction: This work aims to assess the accuracy of robotic assistance guided by a videometric tracker in deep brain stimulation (DBS). Methods: We retrospectively reviewed a total of 30 DBS electrode implantations, assisted by the Remebot robotic system, with a novel frameless videometric registration workflow. Then we selected 30 PD patients who used stereotactic frame surgery to implant electrodes during the same period. For each electrode, accuracy was assessed using radial and axial error. Results: The average radial error of the robot-assisted electrode implantation was 1.28 ± 0.36mm, and the average axial error was 1.20 ± 0.40mm. No deaths or associated hemorrhages, infections or poor incision healing occurred. Conclusion: Ro-bot-assisted implantation guided by a videometric tracker is accurate and safe.